How to develop higher education curricula towards employability? A multi-stakeholder approach - Ôlo, Daniela (2021)
Purpose – This paper aims to find out what conditions are needed to enhance higher education curricula towards employability from the perspective of different stakeholders in the graduate labour market. Design/methodology/approach – An empirical study was developed, using a qualitative approach, based on semi-structured interviews with higher education institutions (HEIs) and labour market players, in the north region of Portugal. The data were analysed through content and descrip\tive analysis with NVivo. Findings – The results show a set of constraints that hinder the match of higher education curricula with employability, namely, (1) theweak connection betweenHEIs and employers and (2) the curricular structure,which is characterised by a heavy theoretical component and a weak approach to the soft skills required by the current labour market. Possible solutions, with implications for educational policy, are given throughout the study. Research limitations/implications – The geographical scope and the nature of the study suggest that some precautions are required when generalising results. However, the literature on other areas in Portugal strengthens the findings and compensates for the sample’s limitations. Originality/value – This study combines the perspectives of the different individual stakeholders involved which, when taken as a whole, provide some recommendations for tailored curricula towards employability. Other studies in Portugal address each of these issues individually, without a connection between all the different perspectives.